PENINGKATAN PENDAPATAN ASLI DESA MELALUI KELEMBAGAN BADAN USAHA MILIK DESA (BUMDES) DESA BANGKIT RAHMAT KECAMATAN JAILOLO SELATAN KABUPATEN HALMAHERA BARAT - Nurdin I Muhammad; Musdar Muhammad (Bajang Institute, 2021)
This Method of Independent PKM Activities Increases Village Original Income Through BUMDes, Focus discussion group (FGD) and Training and monitoring. The result of devotion; Bumdes village Bangkit Rahmat has no income generated, does not have a study of business feasibility, weak purchasing power of the community, human resources are still low, the community still relies on seasonal crops (nutmeg and coconut trees). this devotion provides knowledge to bumdes managers, and provides awareness about mapping the potential of the village, knowledge and understanding to advance the village through BUMDes. This service intends to answer the problem of managing Village Owned Enterprises with a capital statement to BUMDes, but not the existence of village superior goods products as long as village funds are located, village superior / main products, the number of BUMDes business units, This can be seen in the absence of the development of village-owned business entities, does not have a mapping of potential and selection of viable business types in the development of BUMdes in Bangki Rahmat village.